"Doing" ecocriticism: Oppressions of nature and animals in Philip Larkin's poetry. Issue 1 (2nd January 2021) - Idrus, Mohd Muzhafar; Mukahal, Iyad
ABSTRACT: Far fewer studies have investigated Philip Larkin's ecological awareness. While the poet problematizes physical nature and animals, the universal, east-and-west concerns of (non) human beings have been predominantly one-dimensional. This paper analyzes Larkin's poetry, by paying specific attention to the poet's precognition of a looming disaster that ecocritics and environmentalists later came to conceptualize as "the ecological crisis." This article analyzes two poems by Larkin, chiefly, "Going, Going, " and "Take One Home for the Kiddies" in the context of natural environment and animal oppression. Larkin's arguments on the human manipulation of nature eventually disrupl ts the Man-Nature relationship. By focusing on these two of Larkin's poems, the wider application of rhetorical devices attests to the poet's sensitivity, delineating an unstable alliance between human and non-human world(s).